SEASIDE UPCYCLED ART GALLERY: EDUCATIONAL FACILITY TO INCREASE AWARENESS OF WASTE IN PANGANDARAN - Cattleya, Andrea
Indonesia is an archipelago with great water potential, but this country is also facing the problem of marine waste that continues to rise. Based on a study by Jambeck et al. (2015), East Asia is the highest producer of plastic waste into the sea, with Indonesia being the second largest contributor after China. The volume of marine waste in Indonesia reaches 1.29 million tons per year (Ministry of Environment and Forestry, 2023). Pangandaran Beach is one of the most popular tourist destinations in West Java which produces a large amount of marine waste. The waste managed at Pangandaran Beach is divided into two, namely seaborne waste and waste from tourism activities. Seaborne waste is waste from domestic waste that is dumped into rivers, then carried by the river flow to the sea. Waste from tourism activities comes from beach visitors' activities, such as food, beverage, and plastic packaging waste. However, with a waste production of 70-200 tons per day, the existing facilities are considered still inadequate, the existence of waste banks and TPS3R is still not integrated and available in sufficient quantities to meet needs. In response to this problem, this study designs an art gallery that displays handicrafts from recycled plastic waste. The goal is to show the added value of waste carried by the ocean, create awareness of the artistic potential of plastic waste processing. Waste banks and local craftsmen in Pangandaran Beach are also expected to become a basis for collaboration between various parties with diverse backgrounds and goals, to work together to overcome marine ecosystem pollution. Survey data from the Ministry of Tourism and Creative Economy shows that there are around 5 active waste banks in Pangandaran, and the existence of these facilities is expected to strengthen collaboration to deal with the impact of waste on the marine environment. With an educational and recreational approach, this final project aims to raise awareness and community participation in environmental protection efforts in Pangandaran Beach.